THE CHALLENGES IN TEACHING WRITTEN SPEECH - Norkulova Dilnoza Rustam qizi (Galaxy International Interdisciplinary Research Journal, 2023)
The study is to investigate on the challenges of teaching writing for language learning pupils in public schools, especially in school-81 in Surkhandaryo. The work used qualitative method in which different grade English teachers were interviewed to get information about successes and failures, difficulties in teaching writing and pupils were observed in lessons to find problems they face. This article also shows solutions for problems.